Biological Distribution after Oral Administration of Radioiodine-Labeled Acetaminophen to Estimate Gastrointestinal Absorption Function via OATPs, OATs, and/or MRPs - Kakeru Sato; Asuka Mizutani; Yuka Muranaka; Jianwei Yao; Masato Kobayashi; Kana Yamazaki; Ryuichi Nishii; Kodai Nishi; Takeo Nakanishi; Ikumi Tamai; Keiichi Kawai (Pharmaceutics, 2023)
We evaluated the whole-body distribution of orally-administered radioiodine-125 labeled acetaminophen (125I-AP) to estimate gastrointestinal absorption of anionic drugs. 125I-AP was added to human embryonic kidney (HEK)293 and Flp293 cells expressing human organic anion transporting polypeptide (OATP)1B1/3, OATP2B1, organic anion transporter (OAT)1/2/3, or carnitine/organic cation transporter (OCTN)2, with and without bromosulfalein (OATP and multidrug resistance-associated protein (MRP) inhibitor) and probenecid (OAT and MRP inhibitor). The biological distribution in mice was determined by oral administration of 125I-AP with and without bromosulfalein and by intravenous administration of 125I-AP. The uptake of 125I-AP was significantly higher in HEK293/OATP1B1, OATP1B3, OATP2B1, OAT1, and OAT2 cells than that in mock cells. Bromosulfalein and probenecid inhibited OATP- and OAT-mediated uptake, respectively. Moreover, 125I-AP was easily excreted in the urine when administered intravenously. The accumulation of 125I-AP was significantly lower in the blood and urinary bladder of mice receiving oral administration of both 125I-AP and bromosulfalein than those receiving only 125I-AP, but significantly higher in the small intestine due to inhibition of OATPs and/or MRPs. This study indicates that whole-body distribution after oral 125I-AP administration can be used to estimate gastrointestinal absorption in the small intestine via OATPs, OATs, and/or MRPs by measuring radioactivity in the urinary bladder.